Analysis of slips and falls among workers at workplace - Said Ali @ Syed Ali, Sharifah Aznee (2010)
Slips and falls are frequent incidents that occur everywhere either in an office, a school, a factory, a public building or a warehouse, inside and outside. This research focuses on slips and falls incident at workplace only because, workplace is an area that employees are not protected from such hazards. There are several factors that induce slips and fall incidents especially among workers. Although this incident seldom occur but the effect of this accident surely cause various kind problem either to victim or employer. The effects of slips and falls not only cause a small or simple injury, instead it might result in serious injuries such as permanent injury and also result in fatalities. Besides the injuries, the victim also have to support the medical cost and at the same time the victim will loose of their jobs or salary result of the slips and falls incident. Although victim may get their compensation claims from that accident, it would commensurate for victim or victim’s family. Because of such reason, this project will identify the main cause of slips and falls incident among workers at workplace. This project will produce some of suggestion or guidelines that have been identified to overcome the causes of slips and falls.